Genome-wide variation in recombination rate in Eucalyptus. (December 2016) - Gion, Jean-Marc; Hudson, Corey; Lesur, Isabelle; Vaillancourt, René; Potts, Brad; Freeman, Jules
Abstract Background Meiotic recombination is a fundamental evolutionary process. It not only generates diversity, but influences the efficacy of natural selection and genome evolution. There can be significant heterogeneity in recombination rates within and between species, however this variation is not well understood outside of a few model taxa, particularly in forest trees. Eucalypts are forest trees of global economic importance, and dominate many Australian ecosystems. We studied recombination rate inEucalyptus globulus using genetic linkage maps constructed in 10 unrelated individuals, and markers anchored to theEucalyptus reference genome. This experimental design provided the replication to study whether recombination rate varied between individuals and chromosomes, and allowed us to study the genomic attributes and population genetic parameters correlated with this variation. Results Recombination rate varied significantly between individuals (range = 2.71 to 3.51 centimorgans/megabase [cM/Mb]), but was not significantly influenced by sex or cross type (F1 vs. F2 ). Significant differences in recombination rate between chromosomes were also evident (range = 1.98 to 3.81 cM/Mb), beyond those which were due to variation in chromosome size. Variation in chromosomal recombination rate was significantly correlated with gene density (r  = 0.94), GC content (r  = 0.90), and the number of tandem duplicated genes (r  = −0.72) per chromosome. Notably, chromosome level recombination rate was also negatively correlated with the average genetic diversity across six species from an independent set of samples (r  = −0.75). Conclusions The correlations with genomic attributes are consistent with findings in other taxa, however, the direction of the correlation between diversity and recombination rate is opposite to that commonly observed. We argue this is likely to reflect the interaction of selection and specific genome architecture ofEucalyptus . Interestingly, the differences amongst chromosomes in recombination rates appear stable acrossEucalyptus species. Together with the strong correlations between recombination rate and features of theEucalyptus reference genome, we maintain these findings provide further evidence for a broad conservation of genome architecture across the globally significant lineages ofEucalyptus .